Peranan Dinas Perikanan Kabupaten Tulungagung dalam Meningkatkan Kesejahteraan Pelaku Usaha Perikanan: (Studi di Dinas Perikanan Kabupaten Tulungagung) - Slamet Hariyanto; Pratama, Dega Bayu (Universitas Islam Balitar, 2022)
Tulungagung Regency as one of the districts that has a considerable potential for marine waters, makes the development of the role of the Fisheries and Marine Sector in Tulungagung Regency, able to absorb labor and help the community's economy. However, in these two years, the production of capture fisheries in Tulungagung Regency has continued to decline. Nevertheless, the Tulungagung Regency Government through the Fisheries Service still has a high commitment to build and improve facilities and infrastructure in an effort to improve the economy of the fishery business community, so that welfare can be realized for the community, especially those engaged in the fisheries business sector. This research uses a qualitative approach method, which is a research step that explores a deeper picture of looking at all activities in their context. Data collection through interview and observation methods. The subjects determined were the Head of the Fisheries Service, the Head of aquaculture, the head of the capture fisheries sector and the fish farming community. The validity of the data is evidenced by the trianggulation of sources through quality analysis which consists of several procedures such as data reduction, presentation and conclusion making.